MALDI-TOF mass spectrometry for the identification of freshwater snails from Senegal, including intermediate hosts of schistosomes. - Fatima Zohra Hamlili; Fatou Thiam; Maureen Laroche; Adama Zan Diarra; Souleymane Doucouré; Papa Mouhamadou Gaye; Cheikh Binetou Fall; Babacar Faye; Cheikh Sokhna; Doudou Sow; Philippe Parola (Public Library of Science (PLoS), 2021)
Freshwater snails of the genera Biomphalaria, Bulinus, and Oncomelania are intermediate hosts of schistosomes that cause human schistosomiasis, one of the most significant infectious neglected diseases in the world. Identification of freshwater snails is usually based on morphology and potentially DNA-based methods, but these have many drawbacks that hamper their use. MALDI-TOF MS has revolutionised clinical microbiology and has emerged in the medical entomology field. This study aims to evaluate MALDI-TOF MS profiling for the identification of both frozen and ethanol-stored snail species using protein extracts from different body parts. A total of 530 field specimens belonging to nine species (Biomphalaria pfeifferi, Bulinus forskalii, Bulinus senegalensis, Bulinus truncatus, Bulinus globosus, Bellamya unicolor, Cleopatra bulimoides, Lymnaea natalensis, Melanoides tuberculata) and 89 laboratory-reared specimens, including three species (Bi. pfeifferi, Bu. forskalii, Bu. truncatus) were used for this study. For frozen snails, the feet of 127 field and 74 laboratory-reared specimens were used to validate the optimised MALDI-TOF MS protocol. The spectral analysis yielded intra-species reproducibility and inter-species specificity which resulted in the correct identification of all the specimens in blind queries, with log-score values greater than 1.7. In a second step, we demonstrated that MALDI-TOF MS could also be used to identify ethanol-stored snails using proteins extracted from the foot using a specific database including a large number of ethanol preserved specimens. This study shows for the first time that MALDI-TOF MS is a reliable tool for the rapid identification of frozen and ethanol-stored freshwater snails without any malacological expertise.